Importance of the mobility of the clavicle in the scapulohumeral rhythm of the hemiplegic patient (Cuestiones de Fisioterapia, 2002)
Our experience in the treatment of hemiplegic patients, make us deduce that homoalgie is one of the most serious complications in this type of patients. The problem affects not only the superior extremity but the whole-body position. It interferes the patient's daily life, as well as their psychological state and family relationships. Consequently, the period of time for the patient to get himself over is longer than usual and the integration in the social life is also slower. A suitable scapulo-humeral rhythm prevents from homoalgie and what is rally important to get this rhythm is that all the joints of the sacapular belt must be free. Objectives — To show the importance so the scapulo-humeral rhythm ir order to prevent homoalgie in an hemiplegic patient. — To demonstrate the necessity of a correct mobility so the collarbone, as it has to take part in every movement of the scapula. Material and method We have used The Bobath's Method with twenty patients: fifteen males and five females aged bet¬ ween 20 and 70 years old. Eighteen of these patients were hamiplegic because of a cerebrum-vascular accident, and two of them had suffered a cranium-encephalic traumatism. The treatment is initiated with movements of the trunk in order to get a regular tone and a symmetry between the scapula and collarbone, what consequently takes the patient to a correct sitting position, which is necessary to estimulate the reactions of the patient to set himself upright. Right now, is when the rhythm scapulo. humeral can be initiated. Results Fifteen patients from 20 hadn't painful shoulders, two of them showed homoalgies and three of them interrupted the treatment. Conclusions — The patient has to be globally observed, as every part of the body is connected each other. — We have observed that a correct scapulo-humeral rhythm prevents the hemiplegic patient from homoalgie.